The Dialectics of Islamic Religious Education Values in the Artificial Intelligence (AI) Ecosystem: An Analysis of Learning Transformation among Generation Z (A Study of University Students in Pohuwato Regency) - RAHMAT DUNGGIO; Salahudin (DAAR EL-MAKRIFAH: Journal of Islamic Religious Education, 2026)
This study explores the dialectic of Islamic Religious Education (PAI) values within the ecosystem of Artificial Intelligence (AI) and its impact on the transformation of learning among Generation Z students in Pohuwato Regency. Using a qualitative field research approach, the study involved 15 students selected through purposive sampling based on their active use of AI in religious learning. Data were collected through in-depth interviews, observation, and documentation, and analyzed using an interactive model combined with thematic analysis. The findings indicate that AI has become a dominant source of learning, leading to a shift from traditional thalab al-‘ilm practices toward instant and technology-based learning patterns. This transformation also affects the authority of knowledge, where AI is increasingly perceived as an alternative reference, often used without adequate verification. While AI enhances learning effectiveness and supports self-directed learning, it also contributes to the reduction and fragmentation of religious understanding due to its concise and decontextualized responses. Furthermore, the study reveals a value dialectic among students between the convenience of AI and the need for the validity of knowledge. The study concludes that AI has an ambivalent role, offering both opportunities and challenges. Therefore, integrating Islamic values with digital literacy is essential to ensure that AI functions as a supportive tool (wasilah) rather than a primary epistemic authority in Islamic education..